Prediksi Churn Pelanggan Telekomunikasi dengan Optimalisasi Seleksi Fitur dan Tuning Hyperparameter pada Algoritma Klasifikasi C4.5 - Antoh, Soterio; Herteno, Rudy; Budiman, Irwan; Kartini, Dwi; Mazdadi, Muhammad Itqan (Diponegoro University, 2025)
In the telecommunications industry, predicting customer churn is crucial for maintaining business sustainability. High churn rates can negatively impact profitability, necessitating effective retention strategies. This research aims to enhance the accuracy of telecommunications customer churn prediction by optimizing the C4.5 classification algorithm through feature selection and hyperparameter tuning. The methods used include Information Gain for feature selection and hyperparameter tuning with Random Search and Grid Search. This study utilizes the Telco Customer Churn dataset from Kaggle, split into an 80:20 ratio for training and testing data. Six approaches are applied: (1) the basic C4.5 algorithm, (2) C4.5 with Information Gain, (3) C4.5 with Random Search, (4) C4.5 with Grid Search, (5) C4.5 with a combination of Information Gain and Random Search, and (6) C4.5 with a combination of Information Gain and Grid Search. The results indicate that the C4.5 algorithm alone achieves an accuracy of 74.09%, while applying Information Gain increases accuracy to 78.42%. Hyperparameter tuning with Random Search achieves the highest accuracy of 80.05%, whereas Grid Search reaches 77.71%. Combining Information Gain with Random Search results in an accuracy of 78.99%, while combining Information Gain with Grid Search yields an accuracy of 78.85%. These findings suggest that hyperparameter tuning using Random Search significantly improves accuracy compared to other methods, while Information Gain feature selection does not have a significant impact on performance in this context.